BMSC Transplantation Aggravates Inflammation, Oxidative Stress, and Fibrosis and Impairs Skeletal Muscle Regeneration - Liu, Xiaoguang; Zheng, Lifang; Zhou, Yongzhan; Chen, Yingjie; Chen, Peijie; Xiao, Weihua (Frontiers in Physiology, 2019)
keletal muscle contusion is one of the most common muscle injury in sports medicine and traumatology. Bone marrow mesenchymal stem cells (BMSCs) transplantation is a promising strategy for muscle regeneration. However, the roles of BMSCs, especially the mechanisms involved, in the regeneration of contused skeletal muscle are still not fully recognized. Here, we evaluate the potential of BMSCs transplantation for muscle regeneration and mechanisms involved after contusion. BMSCs were immediatelytransplanted into gastrocnemius muscles (GMs) following direct contusion. Morphological and gene expression analyses were used to elevate the effect of BMSCs transplantation and mechanisms involved. The results indicate that BMSCs transplantation impairs muscle regeneration, as well as more fibrotic scar formation after skeletal muscle contusion. Furthermore, macrophages, inflammatory cytokines, chemokines, matrix metalloproteinases and oxidative stress related enzymes were significantly increased after BMSCs transplantation. These results suggest that BMSCs transplantation impairs skeletal muscle regeneration and that macrophages, inflammatory cytokines, chemokines, matrix metalloproteinases and oxidative stress related enzymes may be involved in the process. Taken together, BMSCs transplantation aggravates inflammation, oxidative stress and fibrosis, and impairs skeletal muscle regeneration, which shed new light on the role of BMSCs in regenerative medicine and cautions the application of BMSCs for muscle injury.